Bibliometric analysis on hybrid renewable energy-driven desalination technologies - Ahmed A. Hassan; Mohamed M. Awad (Energy Nexus, 2023)
Throughout human history, water and energy have played pivotal roles in the expansion and progress of societies. However, the availability of fresh water on Earth is limited, constituting less than 3% of the global water resources. Moreover, the distribution of freshwater across countries is inequitable, with a considerable amount being returned to oceans and underground reservoirs. The escalating effects of global warming further disrupt the natural water cycle, posing a serious threat to numerous countries in the form of drought and famine. To meet the increasing demand for freshwater, desalination technologies have been widely employed worldwide. Nevertheless, most of the existing commercial desalination methods heavily rely on fossil fuels and contribute to significant greenhouse gas emissions, exacerbating the issue of global warming. Consequently, the integration of hybrid renewable energy sources into desalination processes emerges as a promising solution to simultaneously address the freshwater demand and combat global warming. So, utilizing hybrid renewable energy supply to drive various desalination technologies is a very promising solution to meet freshwater demands and help mitigating the global warming problem. Therefore, it is imperative to gain a comprehensive understanding of the latest advancements in hybrid renewable energy-driven desalination technologies to guide future research endeavors in this domain. The primary objective of this study is to perform a bibliometric analysis in order to identify the key sources, authors, countries, research institutions, and topics within the field of hybrid renewable energy-driven desalination technologies. By utilizing the R Bibliometrix library and the biblioshiny application, a dataset comprising 451 publications obtained from the Scopus database was analyzed. The results of the analysis reveal a substantial increase in the annual publication rate within this research field over the past five years. Notably, Iran, the United States, and China have emerged as leading contributors in terms of total publications. However, it is noteworthy that countries in the Middle East and the Mediterranean region, in addition to China and the USA, exhibit prominent involvement in various categories of research within this field.